KETIDAKEFEKTIFAN KALIMAT DALAM KARANGAN EKSPOSISI SISWA KELAS VIII SMP NEGERI 15 KERINCI - Oktarina, Reri; Gani, Erizal; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTThis research aim to know about usage of effective sentence at essay exposition of the eighth grade students of SMP Negeri 15 Kerinci. The type of this research is qualitative research with descriptive method. Based on the results of data analysis and discussion, it was concluded the following three points. Firstly, the ineffectiveness of a sentence in terms of the choice of words. Secondly, the ineffectiveness of a sentence in terms of structure. Third, ineffectiveness sentence in terms of punctuation there are three aspects, namely (1) the use of capital letters, (2) writing words in the form of the writing of prepositions in improper, writing preposition to is not precise, and the writing of the word is not right, and (3) use hyphens. Kata kunci: ketidakefektifan, kalimat, karangan eksposisi